Nghiên cứu tổng hợp và đặc trưng xúc tác nanospinel ZnAl2O4. - Thuận, Ngô Thị; Vinh, Nguyễn Hồng; Thu, Hoa Hữu; Mai, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
Nanospinel ZnAl2O4 has been prepared by hydrothermal method and treated thermally at different temperatures under atmospheric pressure. The obtained solids have been characterized by physical methods: DTA, DTG, XRD, TEM and BET. Their physical characteristics showed that the materials synthesized under thermally treating at 600oC were found to be actually the nanospinel ZnAl2O4. Its catalytic activity was measured in oxidehydrogenation of ethylbenzene into stirene in a temperature range 400 to 500oC.